2016
DOI: 10.1039/c6ce00521g
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of citrate-stabilized amorphous calcium phosphate to nanocrystalline apatite: a surface-mediated transformation

Abstract: This is a repository copy of Crystallization of citrate-stabilized amorphous calcium phosphate to nanocrystalline apatite : a surface-mediated transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 33 publications
2
68
0
Order By: Relevance
“…This latter band was not observed in the spectra of samples Col/Ap and Eu-Col/Ap prepared in absence of citrate. It was observed that in all the Raman spectra of the samples prepared using citrate ions in the titrant solutions, the ν 1 PO 4 bands appeared at 951-953 cm -1 indicating the presence of ACP [42] in agreement with the XRD data. In addition it was also observed that the intensity ratio between the peak at 958-959 cm -1 (ν 1 PO 4 ) and that centered at 843-845 cm -1 (νC-C of citrate) is higher when the lowest amount of citrate was used, which confirm that citrate slowed down the growth of apatite and thus behaved as an inhibitor.…”
Section: Ftir and Raman Spectral Featuressupporting
confidence: 79%
“…This latter band was not observed in the spectra of samples Col/Ap and Eu-Col/Ap prepared in absence of citrate. It was observed that in all the Raman spectra of the samples prepared using citrate ions in the titrant solutions, the ν 1 PO 4 bands appeared at 951-953 cm -1 indicating the presence of ACP [42] in agreement with the XRD data. In addition it was also observed that the intensity ratio between the peak at 958-959 cm -1 (ν 1 PO 4 ) and that centered at 843-845 cm -1 (νC-C of citrate) is higher when the lowest amount of citrate was used, which confirm that citrate slowed down the growth of apatite and thus behaved as an inhibitor.…”
Section: Ftir and Raman Spectral Featuressupporting
confidence: 79%
“…For CaP068, CaP078, and CaP088, the Raman bands associated with crystalline CaP (CaHPO 4 , monetite) were distinct and clearly observed. In addition to the ν 1 band at around~987 cm −1 , the ν 2 (~380-430 cm −1 ), ν 3 (at around~1092 and 1129 cm −1 ), and ν 4 (~540-610 cm −1 ) bands were clearly observed for these samples [36][37][38]. The Raman bands marked with asterisk (*) could be attributed to the small amount of calcite in CaP058, CaP068 and CaP078, which was coincident with the PXRD results ( Figure 1b).…”
Section: Synthesis and Characterization Of Acps And Capsmentioning
confidence: 80%
“…The XRD pattern of the ACP phase showed only two very broad and diffuse peaks, which is typical for a pattern lacking periodic LRO [175]. FT-IR and Raman methods use several bands in different vibration domains of PO 4 groups in the phosphate apatite to distinguish ACP [47,176]. Chatzipanagis et al used in situ time-resolved Raman spectroscopy to monitor amorphous phase structural evolution [176].…”
Section: Determination Of Amorphous Phases and Their Solubilitymentioning
confidence: 99%
“…Amorphous calcium carbonate (ACC) is the precursor phase for many invertebrate biomineralizations, such as in the formation of sea urchins [35,36], mollusk shells [23,[37][38][39], and coral skeletons [40]. The transformation of amorphous phases to crystalline phases (Table 1) can occur via several crystallization pathways [21,24,[41][42][43][44][45], such as surface-mediated heterogeneous nucleation [11,[46][47][48], dissolution/re-precipitation [49][50][51][52][53][54][55][56], and solid-solid phase transformation (structure reorganization) [19,33,[57][58][59][60][61][62]. The transformation mechanism and crystallization kinetics depend vitally on the detailed crystallization pathway and on the solution environment [52].…”
Section: Biomineralization Systemsmentioning
confidence: 99%